Pengaruh Tingkat Kecerdasan Ruhaniah terhadap Penyesuaian Sosial Remaja (Studi Deskriptif Kualitatif pada Siswa SMK Negeri 1 Majalaya) - Intan Nuraeni; Muhtar Gojali; Tias Febtiana Sari (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
In development, adolescents experience a period of transition, which some people view as a period of chaos. Therefore, adolescents need adequate ability to interact in order to be able to establish a harmonious relationship with their environment. In this case, the success of the interaction is influenced by the ability to adapt to the environment. Social adjustment can help teenagers to achieve good interactions. Spiritual intelligence is the essence of all intelligence that is in divine values. This study aims to understand the influence of the level of spiritual intelligence on the social adjustment of adolescents in SMK Negeri 1 Majalaya by using a qualitative descriptive research method by interviewing six sources with an age range of 14 years to 17 years who attend SMK Negeri 1 Majalaya. From the data it is known that spiritual intelligence has an influence on the social adjustment of adolescents in SMK Negeri 1 Majalaya. In addition, the research data shows that the six resource persons in this study have good spiritual intelligence and make good social adjustments. Thus, the conclusions in this study indicate a positive relationship between the level of spiritual intelligence on the social adjustment of adolescents at SMK Negeri 1 Majalaya. It is hoped that future researchers will use other methods so that more accurate results are obtained.